The Enhancement of Phytochemical Compounds in Fresh Produces by Abiotic Stress Application at Postharvest Handling Stage - Daimon Syukri; Arisvan Chamel (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2021)
Fresh produces is one of functional food based on its phytochemical contents. The great amounts of the phytochemical compounds in fresh produces become the main core of quality jugdement from fresh produses as a functional food. The use of proper postharvest handling system of fresh produces can be as a tool to protect the loss of the external quality and also can be used to enhance the levels of phytochemical compounds therein at the same time. A good management of plant stresses in respect to key enzymes activation of phytocemicals pathway during postharvest handling treatments of fresh produces can trigger distinct change of contained phytochemicals that can promote their healthy beneficial effect for human life.